Implementasi Pengelolaan Kandang Bebek Hygienis Untuk Meningkatkan Mutu dan Produksi Telur pada Usaha Bebek Petelur di Kelurahan Bontoa Kabupaten Maros - Ummul Masir; Sultan Mubarak Z; Muhammad Kadir (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Increasing duck productivity needs to be done to produce superior and productive livestock, namely implementing intensive duck cultivation, where in an intensive maintenance system, one of the things that must be considered is a healthy and representative cage. This activity aims to sensitize the community on aspects of management and management of duck livestock rearing in a healthier and environmentally friendly type of cage. Empowerment is carried out in the form of awareness through counseling and practice of Hygienic Cage Development Implementation. The results obtained physically in the form of the construction of a healthy and more representative pilot cage for the maintenance of laying ducks. The success of Community Service is also seen from the awareness of the community who want to adopt a more hygienic technique of raising laying ducks through healthy cage management no longer under the house.